2018
DOI: 10.1021/acs.jafc.7b04188
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensing of Pesticides by Zinc Oxide Quantum Dot: An Optical and Electrochemical Approach for the Detection of Pesticides in Water

Abstract: Present study reveals the low concentrations (∼4 ppm) of pesticide sensing vis-à-vis degradation of pesticides with the help of nontoxic zinc oxide quantum dots (QD). In our study, we have taken four different pesticides viz., aldrin, tetradifon, glyphosate, and atrazine, which are widely used in agriculture and have structural dissimilarities/diversity. By using optical sensing techniques such as steady state and time-resolved fluorescence, we have analyzed the detailed exciton dynamics of QD in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…CNTs paste electrodes (CNTPE) were used for determining herbicide fenclorim in soils (Raveendranath Babu et al 2014). Sahoo et al (2018) revealed that ZnO QD could be used to sense low concentrations (,4 mg L À1 ) of four widely used pesticides (aldrin, tetradifon, glyphosate and atrazine) in agriculture. However, despite the above promising findings, few devices are currently being used in commercial agriculture, mainly as a result of the interferences from complex targets, harsh detection environments and high costs (Neethirajan et al 2018).…”
Section: Nano-sensorsmentioning
confidence: 99%
“…CNTs paste electrodes (CNTPE) were used for determining herbicide fenclorim in soils (Raveendranath Babu et al 2014). Sahoo et al (2018) revealed that ZnO QD could be used to sense low concentrations (,4 mg L À1 ) of four widely used pesticides (aldrin, tetradifon, glyphosate and atrazine) in agriculture. However, despite the above promising findings, few devices are currently being used in commercial agriculture, mainly as a result of the interferences from complex targets, harsh detection environments and high costs (Neethirajan et al 2018).…”
Section: Nano-sensorsmentioning
confidence: 99%
“…The water-soluble uorescent ZnO-QDs capped by APTES were prepared following the protocol of Dibakar et al 36,37 Initially, 1% (w/v) carboxymethyl cellulose solution was prepared by dissolving carboxymethyl cellulose powder in double distilled water under stirring at 1500 rpm for 12 h. The uorescent zinc oxide quantum dot capped with APTES (0.5 mg dry weight) were solubilised in 500 mL of double distilled water by ultrasonication for 30 min and added into 5 mL of carboxymethyl cellulose solution followed by incubation under stirring (1500 rpm) for 5 h at 30 C. Now uorescent zinc oxide quantum dotcarboxymethyl cellulose microsphere (ZCM) was prepared by water-in oil emulsion method. The ZCM solution was then added dropwise ($1 mL min À1 ) into 25 mL of light liquid paraffin containing 100 mL of Tween-80 under stirring at 1800 rpm to form water-in-oil emulsion.…”
Section: Preparation Of Microspherementioning
confidence: 99%
“…Given the above disadvantages, an electrochemical sensor (ECS) becomes promising as an inexpensive, fast, portable tool for tracing pesticide residue on a large scale. Nevertheless, background electric signals of the workstation, variable environmental conditions (e.g., temperature, pH and pollutants), diversity among electrodes, and a complex matrix of samples affect the reproducibility of ECS significantly [7,8]. As it is hard to avoid these variations adopting traditional ECS with single-signal In order to resolve this problem, RECS introduces an inner reference signal to build a self-rectification calibration, because the reference probe and target analyte are affected by the same sensing interface.…”
Section: Introductionmentioning
confidence: 99%